Dynamic hedging model of conditional value at risk with options. Issue 4 (3rd July 2016) - Yu, Xing
Abstract: This paper deals with a hedging model in which the methodologies of one-step sliding prediction for variance, MOEAD for multi-objectives optimization are used for the minimization of the conditional value at risk and the cost, maximization of the terminal wealth simultaneously of hedging with options.